Possible scenarios for the spread of mpox outside the endemic focus in Africa - Eskild Petersen; Ulrik Hvid; Oyewale Tomori; Anders Gorm Pedersen; Jacco Wallinga; Richard Pebody; Orlando Cenciarelli; Preben Aavitsland; David Van Laeken; Viggo Andreasen; Uffe Schneider; Julia Kinane Simonsen; et al. (International Journal of Infectious Diseases)
The recent expansion of mpox in Africa is characterized by a dramatic increase in zoonotic transmission (clade Ia) and the emergence of a new clade Ib that is transmitted from human to human by close contact. Clade Ia does not pose a threat in areas without zoonotic reservoirs. But clade Ib may spread widely, as did clade IIb which has spread globally since 2022 among men who have sex with men. It is not clear whether controlling clade Ib will be more difficult than clade IIb. The population at risk potentially counts 100 million but only a million vaccine doses are expected in the next year. Surveillance is needed with exhaustive case detection, polymerase chain reaction confirmation, clade determination, and about severe illness. Such data is needed to identify routes of transmission and core transmitters, such as sex workers. Health care workers are vaccinated to ensure their protection, but this will not curb mpox transmission. With the recent inequitable distribution of COVID-19 vaccines in mind, it is a global responsibility to ensure that low-income nations in the mpox epicenter have meaningful access to vaccines. Vaccination serves not only to reduce mortality in children but limit the risk of future mpox variants emerging that may spread in human populations globally.